Workshop Pembuatan Kain Ecoprint Sebagai Modal Pengetahuan Siswa Menjadi Green Entrepreneur di SMA WR Supratman 1 Medan - Elisabeth Nainggolan; Desma Erica Maryati M; Joni (Jurnal Pengabdian Masyarakat Eka Prasetya, 2023)
Making ecoprint fabric can increase students' insight into how to use the resources in the environment where they live to become a product that can be made easily, environmental friendly and become a product that has economic values if it is marketed and fulfilled the needs of fashion industry. Ecoprint fabric making activities can train students' how to be a creative thinking by arranging leaves as a motif on the fabric and practicing teamwork between other students. With this activity, students have knowledge and understanding that to become an entrepreneur you don't have to exploit nature but you can use nature without destroying it so that the students will be motivated as green entrepreneurs.